Supported Ionic Liquids on Solid Materials as Catalysts for the Synthesis of Propylene Glycol Methyl Ether - Ngoc Haa, Minh; Whiting, Roger; Han, Sheng; Wang, Yuhong (Asian Journal of Chemistry, 2012)
Ionic liquid 1,1,3,3-tetramethylguanidium lactate was immobilized on three solid supports, MCM-41, silica-gel and attapulgite (Atta), by different methods. The prepared materials were used to catalyze the reaction of propylene oxide and methanol to produce propylene glycol methyl ether. 1-Methoxy-2-propanol was the predominant product. The influence of the amount of the catalyst, molar ratio of the reactants, reaction temperature and time on the yield and selectivity was studied. The three catalysts proved to be efficient reusable catalysts for the reaction.